2019
DOI: 10.24293/ijcpml.v26i1.1353
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Alpha Fetoprotein and Platelet Profile in Hepatocellular Carcinoma

Abstract: Hematology abnormalities are commonly found in Hepatocellular Carcinoma (HCC) patients. Platelet (PLT) count in HCC can be low, normal or high, and influenced by tumor and liver damage. There are limited studies about the correlationp between AFP and platelet profile of HCC in Indonesia, especially in Makassar. This study is aimed to analyze the correlation between AFP and platelet profile in HCC patients. A retrospective cross-sectional study was carried out from  January 2016 to June 2017 on 231 HCC subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(4 reference statements)
2
0
0
Order By: Relevance
“…Table 2 Spesific Based on the results of table 1, most gender was treated in the Internal Medicine Inpatient Room at Dr. Soetomo General Academic Hospital because of HCC is male with 43 patients (71.7%). Similar results were also found by Puri et al (2021) and Rahmawati et al (2019) that the male sex is more dominant by 82.5% and 74.9%, respectively. In the Asia Pacific region (especially North and South Korea, Indonesia, and Vietnam), the rate of liver cancer in men is more than 4 times that in women (Zhu et al, 2016).…”
Section: Table 1 General Characteristics Of Hcc Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…Table 2 Spesific Based on the results of table 1, most gender was treated in the Internal Medicine Inpatient Room at Dr. Soetomo General Academic Hospital because of HCC is male with 43 patients (71.7%). Similar results were also found by Puri et al (2021) and Rahmawati et al (2019) that the male sex is more dominant by 82.5% and 74.9%, respectively. In the Asia Pacific region (especially North and South Korea, Indonesia, and Vietnam), the rate of liver cancer in men is more than 4 times that in women (Zhu et al, 2016).…”
Section: Table 1 General Characteristics Of Hcc Patientssupporting
confidence: 90%
“…Platelet levels in patients had an average ± SD and median values of 323,783.33 ± 161,549.5 and 314,000, which indicated normal platelet levels. The same thing happened in the research of Rahmawati et al (2019) and Abdelmoez et al (2019), which showed normal platelet levels in HCC patients. Platelets are closely associated with the occurrence and development of liver diseases, such as hepatocellular carcinoma, nonalcoholic fatty liver disease, viral hepatitis, acute-chronic liver failure, and autoimmune hepatitis (Chen et al, 2020).…”
Section: Table 1 General Characteristics Of Hcc Patientssupporting
confidence: 65%